MODERNITAS KONTEMPORER DAN PROSPEKNYA DALAM ISLAM (BERDASARKAN PEMIKIRAN FAZLUR RAHMAN DALAM ISLAM & MODERNITY) - Abdul Hafith; Taufik; Subhan Abdullah Acim; Jumarim (JCI Publisher, 2025)
Fazlur Rahman is one of the modern Muslim thinkers who plays an important rolein the reconstruction of Islamic thought, especially in responding to the challenges ofmodernity. He argues that Islam is not a static teaching, but rather a dynamic valuesystem that must always develop in accordance with the changing times. One of Rahman'smain criticisms of the Islamic world is the tendency to understand the Qur'an and Sunnahliterally without considering their historical and social context. He offers a double movementmethodology, an approach that traces the original meaning of the text in its historicalcontext, then applies it to modern conditions. This approach allows Islam to remainrelevant without losing its essence. In addition to the interpretation methodology, Rahmanalso contributed to the reform of Islamic education, the integration of science with religion,and the reconstruction of Islamic law based on the principle of maqasid al-shariah. Heemphasized the importance of reopening the door of ijtihad so that Muslims do not getcaught up in taqlid, namely the attitude of accepting Islamic law dogmatically withoutcritical evaluation. Rahman also criticized Islamic fundamentalism which tends to rejectmodernity absolutely, as well as radical secularism which seeks to eliminate the spiritualaspect of human life. According to him, Muslims must be able to adopt the positive aspectsof modernity, such as the development of science and technology, without sacrificingIslamic values. With a more rational and contextual approach, Rahman provides afoundation for Islamic renewal that is not only based on tradition, but also open to thedevelopment of the times. His thoughts offer solutions to various global challenges faced by Muslims, including inlegal, social, and economic aspects. Thus, modernity is not a threat to Islam, but ratheran opportunity to strengthen Islamic values in the lives of contemporary society.